Dual-band microstrip patch antenna array for 5G mobile communications - Rafique, Umair; Khalil, Hisham; Saif-Ur-Rehman (PIERS - FALL : 2017 Progress in Electromagnetics Research Symposium - Fall : 19-22 November 2017, Singapore, 2017)
This paper presents the design of an 8-element microstrip patch antenna (MPA) array for dual-band 5G communications. The proposed antenna array is compact with size of 16× 16 mm 2 at 28 and 38 GHz, respectively. The dual-band response is achieved by etching an inverted U-shaped slot from the main radiator. It is observed from the results that the proposed array is able to provide resonance for desired frequency bands. Furthermore, the proposed antenna array exhibits omni-directional radiations and offer an acceptable gain for both frequency bands.